2021
DOI: 10.21037/jtd-20-3529
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of anxiety and depression in patients with esophageal cancer: underappreciated and undertreated

Abstract: Depression and anxiety are emotional disorders that commonly affect patients with esophageal cancer. As a result of its high morbidity, mortality, and complication rates, this population is at particularly high risk for developing or exacerbating affective disorders; even when compared to patients with other forms of cancer. Many of the medical conditions and social behaviors that predispose patients to this disease are also independently associated with affective disorders, and likely compound their effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…12 This is concerning given that anxiety and/ or depression are linked to poorer health outcomes. 13,42 However, the findings from the current study may yield some promising results for the impact of self-management interventions with regards to mood and well-being of oesophageal cancer survivors.…”
Section: Mood and Hrqolmentioning
confidence: 82%
See 2 more Smart Citations
“…12 This is concerning given that anxiety and/ or depression are linked to poorer health outcomes. 13,42 However, the findings from the current study may yield some promising results for the impact of self-management interventions with regards to mood and well-being of oesophageal cancer survivors.…”
Section: Mood and Hrqolmentioning
confidence: 82%
“…8 However, Liu and colleagues reported clinically significant symptoms of anxiety or depression in up to 23.3% of their participants in their study of psychological distress and Health-Related Quality of Life (HRQoL) 2 years post-surgery. 16 Psychological distress and decreased energy levels have a significant impact on the health and well-being of oesophageal cancer survivors, and have been cited as predictors of poorer survival 13,16,17 following treatment. Qualitative studies lend support to these findings, describing the impact of psychological distress in the recovery period from oesophageal cancer, with many participants identifying the impact of fear of cancer recurrence and pain during post-operative period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies also proved that lower preoperative AGR has a negative correlation to prognosis in gastric cancer [30], bladder cancer [31], and colorectal cancer [32], which consistent with our results. High morbidity, mortality, and complication rates predispose patients with esophageal cancer to emotional distress and psychiatric disorders [33]. Meanwhile, a nationwide population-based longitudinal study showed that the number of EC patients incident psychological distress after surgery increased year by year [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in local care settings, communication between surgical teams, primary care providers, patients, and caregivers is often disorganized and results in significant miscommunication and unnecessary suffering ( 9 ). The financial, emotional, and physical impact of this breakdown in communication and burden results in extraordinarily high suicide ( 10 ) and depression rates ( 11 ) among EC patients. Patients continue to struggle even 15 years from surgery, often with severe symptoms ( 12 ).…”
Section: Introductionmentioning
confidence: 99%